Green low-carbon concrete prepared based on recycled aggregate and preparation method of green low-carbon concrete

By utilizing industrial waste and modified recycled aggregate technology, the problem of low strength of recycled aggregate concrete is solved, and green and low-carbon concrete with good strength and durability is achieved.

CN119874264AActive Publication Date: 2025-04-25CHINA WEST CONSTR GRP +1

Patent Information

Application Number
CN202411930902.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-25
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The performance of existing recycled aggregate concrete is affected by the high water absorption rate of recycled aggregate, and there is a problem of low strength.

Method used

By using industrial waste such as red mud, slag, fly ash, etc., and using benzoxazine and acrylic resin to modify the regenerated aggregate, chemical bonding and polymer network structure are formed, and the strength and toughness of the regenerated aggregate are improved.

Benefits of technology

It significantly improves the compressive strength and durability of concrete, reduces the shrinkage stress during concrete curing, and extends the service life of concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly discloses green low-carbon concrete prepared based on recycled aggregate and a preparation method of the green low-carbon concrete. The green low-carbon concrete is prepared from the following raw materials in parts by weight: 5 to 7 parts of red mud, 10 to 15 parts of slag, 6 to 10 parts of fly ash, 30 to 40 parts of cement, 10 to 15 parts of alkali activator, 20 to 25 parts of modified recycled aggregate, 3 to 5 parts of zeolite powder, 2 to 4 parts of cellulose ether and 40 to 45 parts of water. The preparation method comprises the following steps: weighing the raw material components, adding the red mud, the slag, the alkali activator and half of the water, mixing and stirring to obtain a primary mixture; adding the fly ash, the cement, the modified recycled aggregate, the zeolite powder, the cellulose ether and the remaining water into the primary mixture, and stirring to obtain the concrete. The composition can be used for foundation engineering construction, and has the advantages of high compressive strength and good crack resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and more specifically, to a green low-carbon concrete prepared based on recycled aggregate and a preparation method thereof. Background Art

[0002] With the acceleration of global urbanization, the construction industry has an increasing demand for building materials. At the same time, the construction industry is also one of the main sources of carbon emissions. The production process of traditional concrete not only consumes a large amount of natural resources, such as cement, sand and gravel, but also produces a large amount of greenhouse gas emissions during the production process, which has a serious impact on the environment. In addition, the accumulation of construction waste such as abandoned concrete has also brought serious environmental problems.

[0003] In order to solve the above problems, in recent years, recycled aggregate concrete and geopolymer concrete have gradually attracted attention as new environmentally friendly building materials. Geopolymer concrete is a new type of inorganic cementitious material formed by chemical reaction of inorganic aluminosilicate materials at high temperature. It has the advantages of high strength, high durability, low shrinkage and good environmental friendliness.

[0004] Recycled aggregate concrete uses construction waste such as waste concrete as aggregate, reducing the consumption of natural resources and achieving the reuse of waste. However, the performance of recycled aggregate concrete is often affected by the high water absorption rate of recycled aggregate, resulting in low strength.

[0005] Therefore, how to combine the advantages of recycled aggregates and geopolymers to prepare a high-strength concrete material is a problem that needs to be solved at present. Summary of the invention

[0006] In order to improve the compressive strength of recycled aggregate concrete, the present application provides a green low-carbon concrete prepared based on recycled aggregate and a preparation method thereof.

[0007] In the first aspect, the present application provides a green low-carbon concrete prepared based on recycled aggregate, which adopts the following technical solution: A green low-carbon concrete prepared based on recycled aggregate, comprising the following raw materials in parts by weight: 5-7 parts of red mud, 10-15 parts of slag, 6-10 parts of fly ash, 30-40 parts of cement, 10-15 parts of alkali activator, 20-25 parts of modified recycled aggregate, 3-5 parts of zeolite powder, 2-4 parts of cellulose ether, and 40-45 parts of water.

[0008] By adopting the above technical scheme, industrial wastes such as red mud, slag, and fly ash are fully utilized as raw materials, which not only realizes the recycling of resources, but also significantly reduces the dependence on new raw materials and reduces carbon emissions in the production process. Among them, red mud and slag can react chemically under the action of alkali activators to form geopolymers. This polymer has excellent mechanical properties and durability, providing a solid foundation for concrete. The addition of fly ash further reduces the amount of cement in concrete, reduces costs, and also improves the workability and workability of concrete due to its microbead effect. At the same time, the active ingredients in fly ash can participate in the reaction during the cement hydration process to generate more hydration products and enhance the strength of concrete. In this scheme, cement works synergistically with alkali activators, red mud, slag and other components to form a more compact and stable structure, improving the overall performance of concrete.

[0009] By further modifying the recycled aggregate, the defects of easy water absorption and low strength of the recycled aggregate are improved, and the bonding force between it and other raw materials in concrete is improved, thus obtaining concrete with high strength and good durability.

[0010] In summary, this green low-carbon recycled aggregate low-carbon carbon fixation geopolymer concrete achieves the goal of resource recycling and low-carbon environmental protection through scientific and reasonable raw material ratio. At the same time, its excellent mechanical properties also provide a strong guarantee for the quality and safety of construction projects.

[0011] Optionally, the modified recycled aggregate is modified by a catalyst, an acrylic resin and benzoxazine.

[0012] By adopting the above technical scheme, the ester bonds and carboxyl and other functional groups in the acrylic resin molecules react chemically with the hydroxyl, silicate and other functional groups on the surface of the recycled aggregate to form chemical bonds, and tightly adhere to the surface of the recycled aggregate. At the same time, the unsaturated acid therein can further promote the ring-opening reaction of benzoxazine, generate OH groups, form hydrogen bonds, and form a network structure on the surface of the recycled aggregate, thereby realizing the modification of the recycled aggregate and improving the problems of high water absorption and poor strength of the recycled aggregate.

[0013] At the same time, the modification of benzoxazine makes the recycled aggregate have better toughness and smaller porosity, and reduces the shrinkage of the resin material during the curing process, further improving the strength of the recycled aggregate.

[0014] Optionally, the preparation of the modified recycled aggregate comprises the following steps: (1) After crushing pretreatment of the recycled aggregate, a recycled aggregate with a particle size of 4.75-22.5 mm is obtained; (2) mixing benzoxazine, a catalyst and ethanol and stirring and dispersing them at 90-100° C. for 20-30 minutes to obtain a uniform mixture, adding acrylic resin and continuing to mix and stir and react at a constant temperature for 4-6 hours to obtain a modifier solution; (3) The prepared modifier solution is mixed evenly with the crushed recycled aggregate, and the temperature is gradually increased to 200° C. at a rate of 20° C. / h for solidification, and then cooled to room temperature to obtain the modified recycled aggregate.

[0015] By adopting the above technical solution, benzoxazine undergoes a ring-opening polymerization reaction at high temperature to form a polymer network structure with excellent mechanical properties, giving the recycled aggregate higher strength and toughness. At the same time, the functional groups in the acrylic resin can undergo a cross-linking reaction with the polymerization product of benzoxazine to form a strong chemical bond, which not only enhances the binding force between the modifier solution and the recycled aggregate, but also enables the modifier to more effectively penetrate into the internal pores of the recycled aggregate and fill these pores, thereby further improving the overall strength and density of the recycled aggregate.

[0016] At the same time, the low water absorption property of benzoxazine is utilized, and the modified recycled aggregate is not easy to absorb water. Therefore, when it is used as concrete aggregate for curing, its shrinkage rate is significantly reduced, reducing the generation of internal stress and micro cracks. This not only improves the compressive strength of concrete, but also extends the service life of concrete.

[0017] Optionally, in the preparation step, the weight ratio of the recycled aggregate, benzoxazine and acrylic resin added is 25:2-4:1.5-2.

[0018] By adopting the above technical solution, benzoxazine is used as a core modifier to form a polymer network structure through ring-opening polymerization, and the polymerization product of acrylic resin and benzoxazine undergoes a cross-linking reaction to enhance the bonding force between the recycled aggregate and substrates such as concrete, and fill the pores inside the recycled aggregate to improve its density and strength. By controlling the added weight ratio of each modified raw material within this ratio range, the advantages of each raw material can be fully utilized to form a synergistic effect, and a modified recycled aggregate with high mechanical strength can be prepared. This recycled aggregate not only has excellent physical and chemical properties, but also can play a good bonding and strengthening role in substrates such as concrete, thereby greatly improving the compressive strength of concrete.

[0019] Optionally, the acrylic resin is epoxy acrylate resin.

[0020] By adopting the above technical scheme, an epoxy acrylic resin containing epoxy groups is selected, in which the epoxy groups can undergo cross-linking reactions with other functional groups through ring-opening addition reactions, thereby further densifying the network structure on the surface of the recycled aggregate, thereby further improving the compressive strength of the concrete.

[0021] Optionally, the alkaline activator is a sodium silicate solution.

[0022] By adopting the above technical solution, it is ensured that the sodium silicate solution fully stimulates the activity of the geopolymer cementitious materials red mud and slag to generate more geopolymers. These geopolymers play a skeleton support role in concrete and can significantly improve the compressive strength of concrete.

[0023] Optionally, the raw materials also include 2-4 parts of basalt fibers.

[0024] By adopting the above technical solution, basalt fiber can bridge the tiny cracks in the recycled aggregate and inhibit the expansion of the cracks through its excellent mechanical properties, adding another layer of protection to improve the compressive strength of concrete. Its excellent mechanical properties can further improve the strength of concrete.

[0025] In the second aspect, the present application provides a method for preparing green low-carbon concrete based on recycled aggregate, which adopts the following technical solution: A method for preparing green low-carbon concrete based on recycled aggregate comprises the following steps: (1) weighing each raw material component, adding red mud, slag, alkali activator and half of the water and mixing and stirring to obtain a primary mixture; (2) Add fly ash, cement, modified recycled aggregate, zeolite powder, cellulose ether and the remaining water to the primary mixture and stir to obtain the green low-carbon recycled aggregate low-carbon carbon-fixing geopolymer concrete.

[0026] In summary, this application has the following beneficial effects: 1. This application scheme makes full use of industrial waste such as red mud, slag, fly ash, etc. as raw materials, which not only realizes the reuse of resources and reduces the dependence on new raw materials, but also significantly reduces carbon emissions in the production process. This green and low-carbon raw material selection not only conforms to the concept of sustainable development, but also helps to reduce the pressure on natural resources and reduce environmental pollution. Through scientific and reasonable raw material ratios, the concrete achieves efficient utilization of resources and maximizes environmental benefits while ensuring performance.

[0027] 2. In the present application, benzoxazine and acrylic resin are preferably used to modify the recycled aggregate, and a network structure is formed on the surface of the recycled aggregate through chemical reaction, which significantly improves the water absorption of the recycled aggregate and reduces the internal shrinkage stress during the concrete curing process. At the same time, the modified recycled aggregate has higher strength and toughness, which can further improve the compressive strength of the concrete. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in conjunction with embodiments.

[0029] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0030] Acrylic resin was purchased from Guangzhou Wenjia Chemical Co., Ltd., brand: GA-1700; epoxy acrylate resin was purchased from Langfang Xiangteng Chemical Co., Ltd., model: XH051908; cement was silicate cement purchased from Lingshou County Qianfu Mineral Products Processing Plant, strength grade 42.5; zeolite powder was purchased from Lingshou County Yongshun Mineral Products Processing Plant, SiO 2 The content is 62.5%, 325 mesh; the sodium silicate solution was purchased from Zhengzhou Longfan Chemical Co., Ltd., with a modulus of 3.3; the basalt fiber was purchased from Hebei Sanliujiu New Materials Technology Co., Ltd., with a diameter of 7-25μm and a length of 6-12mm.

[0031] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified recycled aggregate, the preparation of which comprises the following steps: (1) taking the recycled aggregate and putting it into a crusher for crushing and screening to obtain recycled aggregate with a particle size of 4.75-22.5 mm for standby use; (2) 3 kg of benzoxazine, 0.5 kg of 4-dimethylaminopyridine (catalyst) and 30 kg of ethanol were mixed and stirred at 90° C. for 20 min to obtain a uniform mixture, and then 1.5 kg of acrylic resin was added and continued to mix and stir at a constant temperature for 4 h to obtain a modifier solution; (3) 25 kg of the crushed recycled aggregate was taken and mixed with the prepared modifier solution, and the mixture was gradually heated to 200° C. at a rate of 20° C. / h for curing, and then cooled to room temperature to obtain the modified recycled aggregate.

[0032] Preparation Example 2 A modified recycled aggregate, the preparation of which comprises the following steps: (1) taking the recycled aggregate and putting it into a crusher for crushing and screening to obtain recycled aggregate with a particle size of 4.75-22.5 mm for standby use; (2) 2 kg of benzoxazine, 0.5 kg of 4-dimethylaminopyridine (catalyst) and 30 kg of ethanol were mixed and stirred at 100° C. for 30 min to obtain a uniform mixture, and then 2 kg of acrylic resin was added and continued to mix and stir at a constant temperature for 5 h to obtain a modifier solution; (3) 25 kg of the crushed recycled aggregate was taken and mixed with the prepared modifier solution, and the mixture was gradually heated to 200° C. at a rate of 20° C. / h for curing, and then cooled to room temperature to obtain the modified recycled aggregate.

[0033] Preparation Example 3 A modified recycled aggregate, the preparation of which comprises the following steps: (1) taking the recycled aggregate and putting it into a crusher for crushing and screening to obtain recycled aggregate with a particle size of 4.75-22.5 mm for standby use; (2) 4 kg of benzoxazine, 0.5 kg of 4-dimethylaminopyridine (catalyst) and 30 kg of ethanol were mixed and dispersed at 95° C. for 30 min to obtain a uniform mixture, and then 1.75 kg of acrylic resin was added and continued to mix and stir at a constant temperature for 4 h to obtain a modifier solution; (3) 25 kg of the crushed recycled aggregate was taken and mixed with the prepared modifier solution, and the mixture was gradually heated to 200° C. at a rate of 20° C. / h for curing, and then cooled to room temperature to obtain the modified recycled aggregate.

[0034] Preparation Example 4 A modified recycled aggregate is different from Preparation Example 1 in that the weight ratio of recycled aggregate, benzoxazine and acrylic resin added in this Preparation Example is 25:5:3, that is, 25 kg of recycled aggregate, 5 kg of benzoxazine and 3 kg of acrylic resin are added.

[0035] Preparation Example 5 A modified recycled aggregate is different from Preparation Example 1 in that the weight ratio of recycled aggregate, benzoxazine and acrylic resin added in this Preparation Example is 25:1:1, that is, 25kg recycled aggregate, 1kg benzoxazine and 1kg acrylic resin are added.

[0036] Preparation Example 6 A modified recycled aggregate, which is different from Preparation Example 1 in that the acrylic resin used in this Preparation Example is epoxy acrylate resin.

[0037] Comparative Preparation Example 1 A modified recycled aggregate, which is different from Preparation Example 1 in that the modified recycled aggregate used in this Preparation Example is prepared by the following steps: (1) taking the recycled aggregate and putting it into a crusher for crushing and screening to obtain recycled aggregate with a particle size of 4.75-22.5 mm for standby use; (2) 1.5 kg of acrylic resin was mixed with 30 kg of ethanol and stirred at 90° C. for 4 h to obtain a modifier solution; (3) 25 kg of crushed recycled aggregate was mixed with the prepared modifier solution and stirred to mix evenly, and the mixture was gradually heated to 200° C. at a rate of 20° C. / h for curing, and then cooled to room temperature to obtain the modified recycled aggregate.

[0038] Comparative Preparation Example 2 A modified recycled aggregate, which is different from Preparation Example 1 in that the modified recycled aggregate used in this Preparation Example is prepared by the following steps: (1) taking the recycled aggregate and putting it into a crusher for crushing and screening to obtain recycled aggregate with a particle size of 4.75-22.5 mm for standby use; (2) 3 kg of benzoxazine, 0.5 kg of 4-dimethylaminopyridine (catalyst) and 30 kg of ethanol were mixed and stirred at 90° C. for 20 min to obtain a modifier solution; (3) 25 kg of the crushed recycled aggregate was taken and mixed with the prepared modifier solution, and the mixture was gradually heated to 200° C. at a rate of 20° C. / h for curing, and then cooled to room temperature to obtain the modified recycled aggregate. Example

[0039] Example 1 A green low-carbon concrete prepared based on recycled aggregate, the preparation comprising the following steps: (1) weighing each raw material component, adding red mud, slag, alkali activator and half of the water and mixing and stirring to obtain a primary mixture; (2) Add fly ash, cement, modified recycled aggregate, zeolite powder, cellulose ether and the remaining water to the primary mixture and stir to obtain the concrete. In this example, the modified recycled aggregate prepared in Preparation Example 1 is used, and the alkali activator is sodium silicate solution.

[0040] Example 2-3 A green low-carbon concrete prepared based on recycled aggregate is different from Example 1 in that the components of its raw materials and their corresponding weight proportions are shown in Table 1.

[0041] Table 1 Raw materials and their weights in Examples 1-3 (kg) Components Example 1 Example 2 Example 3 Red Mud 6 7 5 slag 15 12.5 10 Alkali activator 6 8 10 Fly ash 8 6 10 cement 40 30 35 Modified recycled aggregate 20 25 22.5 Zeolite powder 4 3 5 Cellulose ether 2 3 4 water 45 40 42.5 Example 4 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that the modified recycled aggregate prepared in Preparation Example 2 is used in this example.

[0042] Example 5 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that the modified recycled aggregate prepared in Preparation Example 3 is used in this example.

[0043] Example 6 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that the modified recycled aggregate prepared in Preparation Example 4 is used in this example.

[0044] Example 7 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that the modified recycled aggregate prepared in Preparation Example 5 is used in this example.

[0045] Example 8 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that the modified recycled aggregate prepared in Preparation Example 6 is used in this example.

[0046] Example 9 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that this embodiment also includes 2 kg of basalt fiber, and the preparation includes the following steps: (1) weighing each raw material component, adding red mud, slag, alkali activator and half of the water and mixing and stirring to obtain a primary mixture; (2) Add fly ash, cement, modified recycled aggregate, basalt fiber, zeolite powder, cellulose ether and the remaining water to the primary mixture and stir to obtain the concrete. In this example, the modified recycled aggregate prepared in Preparation Example 1 is used, and the alkali activator is sodium silicate solution.

[0047] Example 10 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 9 in that 4 kg of basalt fiber is included in this embodiment.

[0048] Comparative Example Comparative Example 1 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that unmodified recycled aggregate is used in this comparative example.

[0049] Comparative Example 2 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that the modified recycled aggregate in Comparative Preparation Example 1 is used in this comparative example.

[0050] Comparative Example 3 A green low-carbon concrete prepared based on recycled aggregate, which is different from Example 1 in that the modified recycled aggregate in Comparative Preparation Example 2 is used in this comparative example.

[0051] Performance testing Detection method / test method Split tensile strength and compressive strength test: The splitting tensile strength and compressive strength of concrete are measured according to the method described in GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete"; Concrete porosity detection: The porosity of the concrete prepared according to the example and comparative example formulations was measured using the mercury intrusion method.

[0052] Table 2 Test results Group 7d splitting tensile strength / Mpa 7d compressive strength / Mpa Porosity / % Example 1 8.59 50.32 3.63 Example 2 8.38 49.17 3.76 Example 3 8.29 49.05 3.98 Example 4 8.32 49.24 3.84 Example 5 8.18 48.94 3.81 Example 6 7.54 47.29 4.12 Example 7 7.62 47.51 4.27 Example 8 8.92 52.13 3.01 Example 9 9.11 53.27 3.14 Example 10 9.2 53.41 3.11 Comparative Example 1 7.23 38.27 7.95 Comparative Example 2 7.42 41.35 5.76 Comparative Example 3 7.38 41.13 5.63 Combining Examples 1-3 and Comparative Example 1 and Table 2, it can be seen that the various test data of Examples 1-3 are better than those of Comparative Example 1, indicating that the defect of easy water absorption of the recycled aggregate can be improved by modifying the recycled aggregate, and the bonding strength of the cement mortar transition zone can be improved, thereby enhancing the strength of the recycled aggregate. At the same time, the modification fills the microcracks in the recycled aggregate, further enhancing the strength of the aggregate, thereby improving the compressive strength and crack resistance of the concrete.

[0053] Combining Examples 1-3 and Comparative Examples 2-3 and Table 2, it can be seen that the various test data of Examples 1-3 are better than those of Comparative Examples 2-3, indicating that by modifying the recycled aggregate with benzoxazine and acrylic resin, a tougher polymer network structure can be formed on the surface of the recycled aggregate, giving the recycled aggregate higher strength and toughness, thereby greatly improving the compressive strength and crack resistance of the concrete prepared therefrom.

[0054] Combining Examples 1-7 and Table 2, it can be seen that the various test data of Examples 1-5 are better than those of Examples 6-7, indicating that the addition ratio of recycled aggregate, benzoxazine and acrylic resin affects the final modification effect when modifying the recycled aggregate. A reasonable ratio can more effectively improve the performance of the recycled aggregate, thereby improving the overall performance of the concrete made from these aggregates.

[0055] Combining Example 1 with Example 8 and Table 2, it can be seen that the various test data of Example 8 are better than those of Example 1, indicating that the epoxy groups inside the epoxy acrylic resin are further used to further participate in the formation of the network structure, thereby enhancing the strength and stability of the surface modified layer of the recycled aggregate, thereby improving the overall performance of the recycled aggregate.

[0056] Combining Example 1 with Examples 9-10 and Table 2, it can be seen that the test data of Examples 9-10 are better than those of Example 1, indicating that further adding basalt fiber to the raw materials can inhibit the expansion of cracks when the concrete is subjected to external force and improve the crack resistance of the concrete.

[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A green low-carbon concrete prepared based on recycled aggregate, characterized in that: The composition comprises the following raw materials in parts by weight: 5-7 parts of red mud, 10-15 parts of slag, 6-10 parts of fly ash, 30-40 parts of cement, 10-15 parts of alkali activator, 20-25 parts of modified recycled aggregate, 3-5 parts of zeolite powder, 2-4 parts of cellulose ether, and 40-45 parts of water.

2. The green low-carbon concrete prepared based on recycled aggregate according to claim 1, characterized in that: The modified recycled aggregate is obtained by modifying a catalyst, an acrylic resin and benzoxazine.

3. The green low-carbon concrete prepared based on recycled aggregate according to claim 1, characterized in that: The modified recycled aggregate preparation comprises the following steps: (1) After crushing and pre-treating the recycled aggregate, a recycled aggregate with a particle size of 4.75-22.5 mm is obtained; (2) Mix benzoxazine, catalyst and ethanol and stir and disperse them at 90-100° C. for 20-30 minutes to obtain a uniform mixture, then add acrylic resin and continue to mix and stir and react at a constant temperature for 4-6 hours to obtain a modifier solution; (3) The prepared modifier solution is mixed evenly with the crushed recycled aggregate, and the temperature is gradually increased to 200° C. at a rate of 20° C. / h for solidification, and then cooled to room temperature to obtain the modified recycled aggregate.

4. The green low-carbon concrete prepared based on recycled aggregate according to claim 3, characterized in that: In the preparation step, the weight ratio of the recycled aggregate, benzoxazine and acrylic resin is 25:2-4:1.5-2.

5. The green low-carbon concrete prepared based on recycled aggregate according to claim 3, characterized in that: The acrylic resin is epoxy acrylate resin.

6. The green low-carbon concrete prepared based on recycled aggregate according to claim 1, characterized in that: The alkaline activator is a sodium silicate solution.

7. The green low-carbon concrete prepared based on recycled aggregate according to claim 1, characterized in that: The raw materials also include 2-4 parts of basalt fibers.

8. A method for preparing green low-carbon concrete made from recycled aggregate according to any one of claims 1 to 6, characterized in that: The steps include: (1) Weighing each raw material component, adding red mud, slag, alkali activator and half of the water, mixing and stirring to obtain a primary mixture; (2) Add fly ash, cement, modified recycled aggregate, zeolite powder, cellulose ether and the remaining water to the primary mixture and stir to obtain the green low-carbon recycled aggregate low-carbon carbon-fixing geopolymer concrete.

Citation Information

Patent Citations

  • High-strength recycled aggregate concrete and preparation method thereof

    CN112010602A

  • Recycled aggregate self-compacting concrete and preparation method thereof

    CN114477873A

  • Low-carbon concrete and preparation method thereof

    CN115417642A

  • Durable recycled aggregate concrete and preparation method thereof

    CN116730679A

Cited By

  • Recycled aggregate concrete 3D printing wall material modification process

    CN120483568A